Sampling terminology / Nurhafizah Ahmad and Fadzilawani Astifar Alias - Ahmad, Nurhafizah; Alias, Fadzilawani Astifar (Unit Penerbitan Dan Publisiti JSKM, 2023)
1 POPULATION : Population is the total entity of people upon which you want to generalize your research. In research, population size is denoted by uppercase letter “N”. 2 SAMPLE : A sample is a part of the population that is drawn from the population. It makes the collection of data and its analysis easy and feasible. Sample size is denoted by lowercase letter “n”. 3 SAMPLE SIZE : The size of the total samples to be taken constitutes the sample size. This is the collection of all the samples taken. Sample size can vary on the following factors: size of the population, variability on the population and required level of accuracy.